Green sol–gel auto combustion synthesis and characterization of double perovskite Tb2ZnMnO6 nanoparticles and a brief study of photocatalytic activity. Issue 14 (19th February 2021) - Dara, Mina; Hassanpour, Mohammad; Alshamsi, Hassan Abbas; Baladi, Mahin; Salavati-Niasari, Masoud
Abstract : In this work, new double perovskite Tb2 ZnMnO6 nanoparticles were successfully synthesized by a sol–gel auto combustion method. Abstract : In this work, new double perovskite Tb2 ZnMnO6 nanoparticles were successfully synthesized by a sol–gel auto combustion method. To synthesize these nanoparticles, three known sugars, lactose, fructose, and maltose, and liquorice powder, which contains quantities of sugar and other organic compounds, were used as fuel. Images obtained from Scanning Electron Microscopy (SEM) analysis implied that maltose-based nanoparticles are homogenous and less in particle size. Further, different maltose ratios were applied to get the best size and morphology. The optimum sample was used to continue the other analysis to check other features of the nanoparticles. Also, the optimum sample was used for the removal of dye contamination under the photocatalytic process. Photocatalytic tests were performed in neutral and alkaline pH conditions under UV-light irradiation. It has been found that the decolorization percent for methyl orange was about 35% and for methyl violet about 55% at neutral pH. Also, this value for methyl violet was about 90% at pH = 8. The results obtained from the study of photocatalytic properties introduce these nanoparticles as a desirable option for removing dye contaminants from aqueous media.